ANALISIS PEMBUATAN PONDASI RUMAH PERMANEN TERHADAP KONSEP ”RUMAH TAHAN GEMPA” DI KABUPATEN BENGKULU UTARA DAN BENGKULU TENGAH - Muhammad Fauzi (Universitas Bengkulu, 2018)
This research purpose to know about people behavior in build permanent house, which see from house foundation reference on the concept of endure earthquake house. This observation have done with the way whice propagated quisioner amount 50 sheet to respondent (craftsman or own house) who building house. This way to find information about building the house. This research have done in North Bengkulu and Middle Bengkulu with took sample in six kecamatan are Air Besi, Arga Makmur, Karang Tinggi, Kerkap,Lais and Pondok Kelapa. This research produced information that making foundation to permanent house building still enough to fill. The concept of endure earthquake house. Because of that,we need a way from goverment in those region,acedemic and all of people to give information about how need build of house appropriate with the concept of endure earthquake house, because Bengkulu province is a earthquake area.